Islam for the Western mind : understanding Muhammad and the Koran - Drummond, Richard Henry (Charlottesville, VA : Hampton Roads Pub. Co., 2005)
"Surveys the life and times of Muhammad and the rise of Islam, including the prophet's visions and the politics that shaped his message"--Provided by publisher.
An overview of issues -- The life of Muhammad, a sketch -- The teaching of the Koran -- Historical and theological evaluation.
Includes bibliographical references (p. 235-240) and index.
Keywords: Muh |ammad, -- Prophet, -- d. 632.; Islam; Islam -- Doctrines